1994
DOI: 10.1152/jappl.1994.76.6.2452
|View full text |Cite
|
Sign up to set email alerts
|

Opioid antagonism alters blood glucose homeostasis during exercise in humans

Abstract: In an attempt to clarify the role of endogenous opioid peptides in substrate mobilization and hormonal responses to dynamic exercise, eight trained cyclists completed exercise trials at 90% of maximal O2 consumption (VO2max) until exhaustion and at 70% VO2max for 90 min. Trials were conducted after intravenous administration of the opiate antagonist naloxone (NAL, 0.1 mg/kg bolus + 0.1 mg.kg-1.h-1) or volume-matched saline (SAL) at each intensity. Serum glucose was maintained at significantly higher levels at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
9
2
Order By: Relevance
“…In contrast, N infusion was reported to induce hyperglycemia at 90 min of exercise despite a signi®cant elevation of the level of plasma C-peptide (Hickey et al 1994). It is unclear why hyperglycemia occurred in this study.…”
Section: Introductioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In contrast, N infusion was reported to induce hyperglycemia at 90 min of exercise despite a signi®cant elevation of the level of plasma C-peptide (Hickey et al 1994). It is unclear why hyperglycemia occurred in this study.…”
Section: Introductioncontrasting
confidence: 69%
“…The signi®cance of BE elevation during exercise remains unclear but BE has been implicated in the glucoregulatory response both at rest (Fatouros et al 1995;Feldman et al 1983;Giugliano et al 1987;Ipp et al 1978;Reid et al 1981) and during exercise (Hickey et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Blockade of EA stimulation-induced increase of plasma insulin was also seen in rats receiving similar treatment with naloxone. Naloxone is often used as a tool in eliciting relations between b-endorphin and plasma glucose homeostasis [23,24]. In diabetic patients, b-endorphin stimulates insulin secretion [19].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the first published work on the identification of endogenous opioids in the pancreas 22 gave rise to studies that focused on the ambiguous mechanisms involved in the endogenous opioid-mediated glucose and insulin homeostasis [23][24][25] . Green et al 24 first showed that morphine and met-enkephalin were able to stimulate glucose-induced insulin release in isolated pancreatic isles, an effect that was observed to develop rapidly, representing the first phase of pancreatic insulin release and which could be blocked by naloxone pre-treatment and therefore, showing an opioid-receptor mediated effect.…”
Section: Introductionmentioning
confidence: 99%